Comparative Mitogenomic Analysis of the Eurydema Genus in the Context of Representative Pentatomidae (Hemiptera: Heteroptera) Taxa. Issue 6 (16th December 2019) - Zhao, Wanqing; Zhao, Qing; Li, Min; Wei, Jiufeng; Zhang, Xianhong; Zhang, Hufang
Abstract: The family Pentatomidae, the largest within the superfamily Pentatomoidae, comprises about 5, 000 species; many of which are economically important pests. Although the phylogeny of Pentatomidae species has been studied using various molecular markers, their phylogenetic relationships remain controversial. Recently, mitochondrial genomes (mitogenomes) have been extensively employed to examine the phylogenetics and evolution of different insects, and in this study, we sequenced complete/near-complete mitochondrial genomes from five shield bug species of Eurydema to gain a better understanding of phylogenetic relationships in the Pentatomidae. The five mitogenomes ranged in length from 15, 500 to 16, 752 bp and comprised 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), 2 ribosomal RNAs (rRNAs), and a control region. We compared mitogenomic characteristics of the Pentatomidae and constructed phylogenetic trees using Bayesian inference and maximum likelihood methods. Our results showed that gene arrangements, base composition, start/stop codons, gene overlaps, and RNA structures were conserved within the Pentatomidae and that congeneric species shared more characteristics. Saturation and heterogeneity analyses revealed that our PCGs and PCGRNA datasets were valid for phylogenetic analysis. Phylogenetic analyses showed consistent topologies based on BI and ML methods. These analyses strongly supported that Eurydema species belong to the tribe Strachiini, and formed a sister group with Pentatomini. The relationships among Eurydema species were shown to be consistent with their morphological features. (Strachiini + Pentatomini) was found to be a stable sibling of the clade comprising Cappaeini, Graphosomini, and Carpocorini. Furthermore, our results indicated that Graphosoma rubrolineatum (Heteroptera: Pentatomidae) belongs to the Pentatominae and not the Podopinae.